Monetary mythology: the West German central bank and historical narratives, 1948-78 - Mee, S (2016)
This thesis examines the emergence, and then development, of what I call 'monetary mythology', a historical narrative, or version of history, concerning the inter-war period of Germany. Following the Second World War, it was left to West German elites to establish a new federal central bank, the Deutsche Bundesbank. A three-way power struggle emerged between the existing West German central bank – the Bank deutscher Länder - the federal government and the various state governments, all vying to influence the institutions and structure of this new monetary authority. In justifying their arguments, West German elites used various lessons derived from the turbulent experiences of the inter-war era. Monetary mythology, for its part, emphasised the lessons of Germany's two inflations; and the Bank deutscher Länder, and its allies, explicitly tied these lessons to the need for an independent central bank. And though it was once challenged by other competing historical narratives in the period 1949-51, monetary mythology emerged by 1956 triumphant in the public sphere in terms of framing the parameters through which West Germans viewed their monetary history. The doctoral project at hand approaches economic history from a cultural angle. In doing so, it offers an alternative history of the Bundesbank, as well as an alternative explanation for the cultural preoccupation surrounding inflation in West Germany. The thesis explains this cultural preoccupation in institutional terms. In providing for a central bank that was independent of political instruction, the Bundesbank Law of 1957 allowed for conflicts between the federal government and central bank to emerge. These conflicts often became 'dramatised' in the public sphere, creating controversies surrounding the Bundesbank's independence, and, in turn, giving rise to circumstances in which the lessons of the two inflations continued to remain relevant, geared in support of central bank independence.